Robust Multiobjective Optimization of Cutting Parameters in Face Milling - (:unkn) unknown (BUDAPEST TECH, 2012)
In this paper, a new multiobjective optimization approach is proposed for the selection of the optimal values for cutting conditions in the face milling of cobalt-based alloys. This approach aims to handle the possible manufacturing errors in the design stage. These errors are taken into consideration as a change in design parameter, and the design most robust to change is selected as the optimum design. Experiments on a cobalt-based superalloy were performed to investigate the effect of cutting speed, feed rate and cutting depth on the cutting forces under dry conditions. Material removal rate values were also obtained. Minimizing cutting forces and maximizing the material removal were considered as objectives. It is believed that the used method provides a robust way of looking at the optimum parameter selection problems.
Keywords: face milling; robust optimization; cobalt-based superalloy; sensitivity; multiobjective optimization; optimum cutting parameters; WEIGHTED SUM METHOD; SENSITIVITY-ANALYSIS; MICROSTRUCTURE; WEAR